Defect levels from SCAN and MBJ meta-GGA exchange-correlation potentials - Rauch, Tomas; Munoz, Francisco; Marques, Miguel A. L.; Botti, Silvana (Physical Review B, 2021)
For more than a decade the HSE06 hybrid exchange-correlation functional developed by Heyd, Scuseria and Ernzerhof has provided a tool for reliable defect level calculations in density functional theory for which postprocessing tools are not necessary, in contrast to previous calculations using semilocal density functionals. One of the main reasons for its reliability is the high precision of HSE06 for band gap calculations. Recently, other functionals from the meta-generalized gradient approximation (meta-GGA) class have been used extensively to calculate the electronic properties of solids. In particular, band gaps can be accurately evaluated with the modified Becke-Johnson (MBJ) potential, and relaxed atomic structures close to experimental findings can be obtained with the strongly constrained and appropriately normed (SCAN) exchange-correlation functional. Both approaches are computationally cheaper than HSE06, and we consider here their performance for defect level calculations. We compare results for the ϵ(+/0) transition levels of seven donors and ϵ(0/-) transition levels of four acceptors in group IV semiconductors. We conclude that in certain situations where HSE06 cannot be applied because of excessive computational costs, SCAN and MBJ might provide a good alternative.
CRIS-Team Scopus Importer:2023-04-20